Dwie podroze Guliwera - Swift, Jonathan, 1667-1745.; Lebkowski, Miroslaw; Werner, Stanislaw (Warszawa : Wydawn. Tenten)
A selection of stories from Gulliver's travels. Ages 8-12.
Selected translation of: Gulliver's travels.
Keywords: Gulliver, Lemuel (Fictitious character) -- Juvenile fiction; Satire, English; Voyages, Imaginary -- Early works to 1800.